APLIKASI JAMUR MIKORIZA ARBUSKULAR DAN PUPUK ANORGANIK PENGARUHNYA PADA PERTUMBUHAN DAN HASIL JAGUNG MANIS - Pauliz Budi Hastuti; Neny Andayani; Muhammad Shabri Sidiq (Program Studi Agroteknologi INSTIPER, 2021)
This study aims to determine the effect of the dose of arbuscular mycorrhiza fungi (AM) and the administration of inorganic fertilizers on the growth and yield of sweet corn. This research was conducted in Kota Bangun Village, Tapung Hilir, Kampar, Riau in June to August 2020. The experimental design used was a completely randomized design consisting of two factors and four replications. The first factor was the dose of AM fungi consisting of 4 levels, namely 0 g / plant, 10 g / plant, 15 g / plant, 20 g / plant. The second factor was the administration of inorganic fertilizer consisting of 4 levels, namely (6 g NPK + 4 g urea)/plant, (4.5 g NPK + 3 urea)/plant, (3 g NPK + 2 g urea)/plant, (1.5 g NPK + 1 g urea)/plant. The observations were analyzed using Analysis Of Variance (ANOVA) at a level of 5%, a significantly different among treatment in further tests with Duncan's Multiple Range Test (DMRT) at a level of 5%. The results showed that there was no good combination the dose of AM fungi and inorganic fertilizers on the growth and yield of sweet corn crops. The dose of AM fungi 10 g / plant gives a better influence on diameter of stem and the percentage of AM infection, inorganic fertilizer administration dose (6 g NPK + 4 g urea) produces the best cob weight. Keywords: Sweet Corn, Mycorrhiza Arbuscular, Inorganic Fertilizer